Role for the microtubule-associated protein tau variant p.A152T in risk of α-synucleinopathies. (10th November 2015) - Labbé, Catherine; Ogaki, Kotaro; Lorenzo-Betancor, Oswaldo; Soto-Ortolaza, Alexandra I.; Walton, Ronald L.; Rayaprolu, Sruti; Fujioka, Shinsuke; Murray, Melissa E.; Heckman, Michael G.; Puschmann, Andreas; McCarthy, Allan; Lynch, Timothy; et al.
Abstract : Objective: To assess the importance of MAPT variant p.A152T in the risk of synucleinopathies. Methods: In this case-control study, we screened a large global series of patients and controls, and assessed associations between p.A152T and disease risk. We included 3, 229 patients with clinical Parkinson disease (PD), 442 with clinical dementia with Lewy bodies (DLB), 181 with multiple system atrophy (MSA), 832 with pathologically confirmed Lewy body disease (LBD), and 2, 456 healthy controls. Results: The minor allele frequencies (MAF) in clinical PD cases (0.28%) and in controls (0.2%) were not found to be significantly different (odds ratio [OR] 1.37, 95% confidence interval [CI] 0.63–2.98, p = 0.42). However, a significant association was observed with clinical DLB (MAF 0.68%, OR 5.76, 95% CI 1.62–20.51, p = 0.007) and LBD (MAF 0.42%, OR 3.55, 95% CI 1.04–12.17, p = 0.04). Additionally, p.A152T was more common in patients with MSA compared to controls (MAF 0.55%, OR 4.68, 95% CI 0.85–25.72, p = 0.08) but this was not statistically significant and therefore should be interpreted with caution. Conclusions: Overall, our findings suggest that MAPT p.A152T is a rare low penetrance variant likely associated with DLB that may be influenced by coexisting LBD and AD pathology. Given the rare nature of the variant, further studies with greater sample size are warranted and will help to fully explain the role of p.A152T in the pathogenesis of the synucleinopathies.